Synthesis and Biological Evaluation of New Madecassic Acid Derivatives Targeting ERK Cascade Signaling - Valdeira, Ana S. C.; Ritt, Daniel A.; Morrison, Deborah K.; McMahon, James B.; Gustafson, Kirk R.; Salvador, Jorge A. R. (Frontiers in Chemistry, 2018)
In the present study, a series of novel madecassic acid derivatives was synthesized and screened against the National Cancer Institute’s 60 human cancer cell line panel. Among them, compounds 5, 12 and 17 displayed potent and highly differential antiproliferative activity against 80% of the tumor cells harboring the B-RafV600E mutation within the nanomolar range. Structure-activity analysis revealed that a 5-membered A ring containing an α,β-unsaturated aldehyde substituted at C-23 with a 2-furoyl group seems to be crucial to produce this particular growth inhibition signature. In silico analysis of the cytotoxicity pattern of these compounds identified two highly correlated clinically approved drugs with known B-RafV600E inhibitory activity. Follow-up analysis revealed inhibition of the ERK signaling pathway through the reduction of cellular Raf protein levels is a key mechanism of action of these compounds. In particular, 17 was the most potent compound in suppressing tumor growth of B-RafV600E-mutant cell lines and displayed the highest reduction of Raf protein levels among the tested compounds. Taken together, this study revealed that modifications of madecassic acid structure can provide molecules with potent anticancer activity against cell lines harboring the clinically relevant B-RafV600E mutation, with compound 17 identified as a promising lead for the development of new anticancer drugs.